PARTIAL RENAL FUNCTIONS AND FLUID-AND-ELECTROLYTE BALANCE IN EXPERIMENTAL FLUOROSIS - Татьяна Константиновна Ядыкина; Лариса Геннадьевна Горохова; Татьяна Георгиевна Корсакова (Медицина в Кузбассе, 2017)
Objective. The study on the changes in the fluid-and-electrolyte balance of the body and partial renal functions in the dynamics of the development of experimental fluorosis.